2012
DOI: 10.1155/2012/873804
|View full text |Cite
|
Sign up to set email alerts
|

Color Dependence on Thickness in Topaz Crystal from Brazil

Abstract: It is well known that crystals of topaz from the Eastern Brazilian Pegmatite Province may turn blue by the irradiation with 60 Co gamma rays followed by heat treatment. Also, it is known that the sensation of color changes with the thickness of these crystals. The dependence of the color, given by 1931 CIE chromaticity coordinates, with the thickness of the crystal was analyzed. The absorbance used in the calculation of these coordinates was given by the sum of Gaussian lines. The parameters of these lines wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…1, curve 4). Two lines around 230 and 305 nm belong to a single defect such as silanone (=Si=O) as it was suggested in [28] based on similar lines observed in spodumene. A blue color is related to a broad absorption band in the red part of the spectrum generated by the socalled R-centers (two F-vacancies with two trapped electrons) [29].…”
Section: Resultssupporting
confidence: 66%
“…1, curve 4). Two lines around 230 and 305 nm belong to a single defect such as silanone (=Si=O) as it was suggested in [28] based on similar lines observed in spodumene. A blue color is related to a broad absorption band in the red part of the spectrum generated by the socalled R-centers (two F-vacancies with two trapped electrons) [29].…”
Section: Resultssupporting
confidence: 66%
“…After irradiation in absorption spectra there appears an intense absorption at 230 nm and occur the characteristic maxima at 305, 410, 446, ~590 nm. Two lines around 230 and 305 nm belong to a single defect such as silanone (=Si=O) as it was suggested in [9] basing on similar lines observed in spodumene. Blue color is connected with a broad absorption band in the red part of the spectrum generated by the so-colled R-centers (two F-vacancies with two trapped electrons) [10].…”
Section: A Topaz Crystalssupporting
confidence: 70%
“…In the figure the well-defined absorption band is observed at 620 nm under the influence of a strong absorption in the ultraviolet region. A recent study indicates that the strong absorption observed below 400 nm in the present spectrum is due to an optical absorption band around 314 nm and that this band can be tentatively assigned to silanone (QSiQO) [14]. A small and broad shoulder of the 620 nm band appears in the region of 800-1100 nm.…”
Section: Methodssupporting
confidence: 48%